Pusa Purvi: New variety of small fruited bitter gourd - Behera, T K; Munshi, A D; Rana, S C (Indian Horticulture, 2023)
Pusa Purvi has been released and notified by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for cultivation in National Capital Region of Delhi and its adjoining areas. The growers will be benefitted by this variety because of its prolific bearing, better nutritional quality and organoleptic taste.